Judicial cooperation on money laundering in the WAEMU space : current situation and prospects - (:unkn) unknown (My University, 2019)
In West Africa, the West African Economic and Monetary Union (WAEMU) is firmly committed to combating money laundering. Within the framework of its mutual legal assistance, the WAEMU established mechanisms to facilitate cooperation in criminal-related matters such enabling sharing of information and evidence between its Member States during investigation processes and then contributing to the successful accomplishment of those investigations. Extradition has also been redefined in such a way as to ensure its procedural requirements are more flexible and simplified. However, the existence of these legal mechanisms does not necessarily mean that judicial cooperation will experience better days in the short term within the WAEMU space. Indeed, it will still be facing many challenges.Therefore, the analysis of the current general framework of international judicial cooperation within Member States of the WAEMU appears as a necessity. It will be focusing on the impact that the current judicial cooperation may have in the eradication of the phenomenon of corruption and money laundering in this part of the African continent. To that effect, the model of judicial cooperation between Member States of the European Union could serve as a basis for reflection.
Keywords: African Research